Chen Duxiu, Founder of the Chinese Communist Party - Feigon, Lee, 1945- (Book collections on Project MUSE., 1983)
This book is the first complete study of Chen Duxiu, the controversial founder and first secretary-general of the Chinese Communist party. Disputing many conventional views of the New Culture movement and the early history of the party, Lee Feigon examines the social and political context of Chen's ideas and actions, particularly his relationship with the early Chinese youth movement. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.